UMPSA now possesses Floating Solar Panels - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
PEKAN, 2 November 2023 – The Chairman of the Board of Directors of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Dato' Seri Abdul Razak Jaafar, made an official visit for the first time to the university since his appointment as Chairman of the Board of Directors, effective November 1, 2023.